Scratch resistance of brittle thin films on compliant substrates - Wu, Linda Y. L. (2012)
There has been intensive interest in studying the behavior of hard and brittle thin films on compliant substrates under scratch action. The examples include sol–gel protective coatings on plastic optical lenses, safe windows, and flexible electronic devices and displays. Hard ceramic coatings have been widely used to prolong the life of cutting tools and biomedical implants. In this work, the scratch resistance of sol–gel coatings with different amount of colloidal silica on polycarbonate substrates was tested by the pencil scratch test following the ISO 15184 standard. The scratch failure was found to be tensile trailing cracking in the coating and substrate gouging. The indentation hardness, elasticity modulus and fracture toughness of the coatings were determined and correlated to the observed pencil scratch hardness. Based on the analysis, the main factors to improve the scratch resistance are the elasticity modulus, thickness and fracture toughness of the coatings. General consideration for the improvement of scratch resistance of hard coatings on compliant substrates was also discussed.